Factors Influencing Tourists Revisit to Bali as Mice Destination - Mahadewi, Ni Made Eka; Bendesa, I Komang Gde; Antara, Made (E-Journal of Tourism; Volume 1 Number 1 (March 2014), 2014)
Plan to revisit of MICE tourists has been highlighted as an important research topic in competitive market of tourism destinations especially in MICE Destination. Despite the considerable number of research on MICE tourists, it remains unclear why MICE tourists undertake to plan their repeated visits and what kind of indicators influenced. This research aims to identify factors influencing MICE tourists to revisit to Bali – Indonesia. By using SEM (Structural Equation Model), one of the results of this study indicated that MICE Destination’s attribute, Promotion, Satisfaction and Image were the important factor to affect Revisit of MICE tourists to come again or revisit to Bali as MICE Destination. Concerning with MICE tourists perception on revisit; tourist visit to Bali for MICE destination can be enhanced by promotion through image of Bali.
Keywords: MICE destination; Promotion; Image; Revisit